(untitled) (American Journal of Interdisciplinary Research and Development, 2023)
This article is about the family of coronaviruses, the causative agent of the COVID-19 disease, its morphological structure, the importance of glycoproteins in binding to the cell, the areas of the ASE2 receptor located in the body, the processes that occur in the pathogenesis of the disease, the storm of cytokines, biochemical changes in the blood, the symptoms of the disease and the characteristics of the course of side effects after vaccination.